Turbine wheel reduced modal model for self-excited vibration suppression by inter-blade dry-friction damping - Pešek, Luděk; Šnábl, Pavel; Prasad, Chandra Shekhar (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
A new approach to calculations based on the modal synthesis method is proposed for the evaluation of structural and dry-friction damping effects on self-excited vibrations due to aeroelastic instability in bladed turbine wheels. The method described herein is used to study dry-friction damping of self-excited vibration of an industrial turbine wheel with 66 blades. For evaluating damping effects, the blade couplings are applied to this particular turbine wheel. Therefore, neighbouring blades are interconnected by rigid arms that are fixed on one side to one blade and are in frictional contact on their free side with the other blade. Due to relatively normal motions in contacts, the prescribed contact forces vary over time. The aerodynamic excitation arises from the spatially periodical flow of steam through the stator blade cascade. In this paper, we attempt to model flow-induced instabilities with the Van der Pol model linked to relative motion between neighbouring blades. The proposed modal synthesis method as ROM is a computationally efficient solution allowing substantial parametrization. The effect of the angles of contact surfaces on the wheel dynamics and on the level of the self-excitation suppression will be discussed herein.